SYNTHESIS AND CHARACTERIZATION OF HCL DOPED POLYANILINE USING DIRECT OXIDATION METHOD WITH VARIOUS STIRING DURATION AT TEMPERATURE OF 0 AND 25 oC - AYU PRATIWI (NIM : 10508097);Pembimbing I : Dr. Veinardi Suendo; Pembimbing II : Dr. Ac, MEGA
Polyaniline is one of conducting polymer which is widely used in industry as the starting material for solar cells, battery, and gas sensor. Those applications usually need polyaniline with high conductivity. Previous research found that stirring during synthesis highly affects the structure and the conductivity of polyaniline. In this research polyaniline is doped by HCl with direct oxidation method using ammonium peroxodisulfate (APS) as the oxidator at 0 and 25OC. Here, the total time of synthesis is kept constant for 48 hours, while the strirring duration are varied for 48, 36, 24, 12, 6, 3, 1, and 0 (without strirring) hours. The total time of synthesis is approximately 48 hours. The dark green polyaniline powder is produced and characterized using Raman Spectrocopy, FTIR, XRD, SEM, and EIS. SEM results show that the size of polyaniline particles is increases with longer stirring duration. XRD results show there is an expansion of diffraction plane {(110)} from the shift of diffraction angle 2θ, from 25.5 to 25O, as the function of stirring duration. Raman spectra also show a shift for whole spectra to the higher wavenumber effected by stirring. Infrared spectra show that quinoid, benzoid, and aromatic C-H appear at 1557 cm-1,1477 cm-1, and 1302 cm-1. EIS data show that the longer stirring duration leads to the growth of polyaniline with lower conductivity in the range of 0,1-0,03 S cm-1.